Vertical dimonsion changes after muscle relaxation - Shahroodi MH (Tehran University of Medical Sciences, 1998)
In this study, 116 edentulous patients in the age group 37-90 yrs were selected. Out of the above,"n12 patients had visited the dept. Of prosthodontics for the first time for treatment. Other 34 of them were"npatients of the dental school and the rest were from Kahrizak and Nikan sanatoriums."nInitially, the V.D. of rest was measured as usual for all the patients. After subjecting them to the excercises of completely opening and closing of the mouth for 15 no. of times, the rest position was measured again. Results show that the changes in V.D.R. after, excercises, relaxing the elevator and depressor muscles and the duration of usage of prosthesis, the following conclusions are obtained."n1. There is an increase in V.D.R. after tiring out the elevator and depressor muscles of the jaws."n2. There is a direct co - relation between the increased V.D.R. and duration of use of prosthesis after excercises."n3. Change in the V.D.R. after excercise is notably more in women."n4. No definite conclusion is obtained in the relationship between changes in V.D.R. after excercises and use of prosthesis during sleep."n5. As above no conclusions as yet can be deduced between changes in V.D.R. and different operators.